2020
DOI: 10.1177/1043659620976803
|View full text |Cite
|
Sign up to set email alerts
|

Prejudiced Attitudes of Nursing Students in Southern Spain Toward Migrant Patients

Abstract: Introduction The increase in the migrant population in Spain has transformed the cultural profile of public health care users. The purpose of this study is to recognize the subtle and blatant prejudices nursing students have toward migrant patients. Method An ex post facto descriptive study, using a transversal design ( N = 1,393). Results Males showed a higher degree of prejudice ( p < .05). Students in their first year have more subtle prejudices than those in their fourth year ( p < .005). Blatant pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…Men’s NATIS scores were significantly higher than women’s, and men had a more negative attitude toward immigrants. Similar to our study, in a study conducted with nursing students in Spain, male students had more negative attitudes toward immigrants (Alemany-Arrebola et al, 2021). A study conducted with nursing students in Portugal found that gender was not an influential factor in attitudes toward immigrants, with women agreeing that the coexistence of different cultures promotes knowledge sharing and mutual respect.…”
Section: Comparison Of Scale Scores According To Sociodemographic Fin...supporting
confidence: 88%
See 1 more Smart Citation
“…Men’s NATIS scores were significantly higher than women’s, and men had a more negative attitude toward immigrants. Similar to our study, in a study conducted with nursing students in Spain, male students had more negative attitudes toward immigrants (Alemany-Arrebola et al, 2021). A study conducted with nursing students in Portugal found that gender was not an influential factor in attitudes toward immigrants, with women agreeing that the coexistence of different cultures promotes knowledge sharing and mutual respect.…”
Section: Comparison Of Scale Scores According To Sociodemographic Fin...supporting
confidence: 88%
“…In the study in which 116 nursing students participated, it was found that the educational content provided on cultural care would reduce negative attitudes toward immigrants and contribute to the adoption of the importance of intercultural care (Sánchez-Ojeda et al, 2021). In the context of intercultural nursing, it is essential to include prejudiced attitudes toward immigrants, environment-culture relationship (Gurrutxaga et al, 2019), health services compatible with the patient’s culture (Akgül Gündoğdu et al, 2022; Jin et al, 2020), including cultural care guidelines and practices related to avoiding discriminatory behaviors in the nursing education curriculum (Alemany-Arrebola et al, 2021; Sánchez-Ojeda et al, 2020). In line with these findings that the negative impact of the cultural difference of individuals on the treatments and care approach, the increase in the cultural sensitivity levels of nursing students with education prevents them from displaying negative attitudes toward immigrants.…”
Section: Comparison Of Scale Scores According To Sociodemographic Fin...mentioning
confidence: 99%
“…Education in social determinants of health, social justice, and sociocultural competence should be an essential element integrated throughout the degree programs. These points are insufficiently taught in nursing programs (Alemany-Arrebola et al, 2021; Demirtas et al, 2021; Habibzadeh et al, 2021). Moreover, no research has been found in which students reflected about how the virus influences those at a higher risk of suffering its wider consequences (specifically in ethnic minorities and socioeconomically vulnerable groups).…”
Section: Discussionmentioning
confidence: 99%